Estimation of technical efficiency for share contract of producing gum Arabic: Kordofan gum Arabic belt, Sudan - Elkhidir, Elrashied Elimam; Baharumshah, Ahmad Zubaidi; Tai, Shzee Yew (Academic Journals, 2010)
The purpose of this study was to estimate the production technical efficiencies for share contract of producing gum arabic and to test whether sharecropping is an efficient mode of production in Kordofan gum arabic belt farming system. A paird sample of 40 gum producers who operate owned and shared orchards and represent different share contract arrangements was selected. The study utilizes stochastic frontier production functions to calculate technical efficiency scores. Land, gum trees capital services flow, family and hired labours and tapping intensities as inputs in frontier production function have significant effects on gum arabic yield. Moreover, the technical inefficiency effects that are assumed to be functions of age and education of mixed sharecroppers, amount of rainfall, soil type and different share contract arrangements were significantly affected the technical efficiency levels. Results revealed that 98% of the shared orchards of mixed sharecropping farmers have technical efficiency less than 50% while only 12.5% of owned orchards are less than this technical efficiency level. This recommends that the mixed sharecropping farmers are less efficient in allocating their input resources in shared than owned orchards.